2017
DOI: 10.1371/journal.pone.0176315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature and soil type on Mycobacterium bovis survival in the environment

Abstract: Mycobacterium bovis, the causative agent of the bovine tuberculosis (bTB), mainly affects cattle, its natural reservoir, but also a wide range of domestic and wild mammals. Besides direct transmission via contaminated aerosols, indirect transmission of the M. bovis between wildlife and livestock might occur by inhalation or ingestion of environmental substrates contaminated through infected animal shedding. We monitored the survival of M. bovis in two soil samples chosen for their contrasted physical and-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…M. bovis in faeces or faeces-contaminated soil appears to remain viable for up to ~6 months in some studies ( 193, 194 ). More recently, Barbier et al ( 195 ) have undertaken in vitro experiments in which differing soil types were seeded with M. bovis and incubated at 4 and 22˚C. Their findings indicated that M. bovis persisted for longer (up to 150 days) at the cooler temperature, whilst results for differing soil types were inconclusive ( 195 ).…”
Section: Climate and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…M. bovis in faeces or faeces-contaminated soil appears to remain viable for up to ~6 months in some studies ( 193, 194 ). More recently, Barbier et al ( 195 ) have undertaken in vitro experiments in which differing soil types were seeded with M. bovis and incubated at 4 and 22˚C. Their findings indicated that M. bovis persisted for longer (up to 150 days) at the cooler temperature, whilst results for differing soil types were inconclusive ( 195 ).…”
Section: Climate and Environmentmentioning
confidence: 99%
“…More recently, Barbier et al ( 195 ) have undertaken in vitro experiments in which differing soil types were seeded with M. bovis and incubated at 4 and 22˚C. Their findings indicated that M. bovis persisted for longer (up to 150 days) at the cooler temperature, whilst results for differing soil types were inconclusive ( 195 ). It may also be worth investigating whether M. bovis strain variation may have a role to play in adaptation to environmental persistence.…”
Section: Climate and Environmentmentioning
confidence: 99%
“…Environmental contamination with M. bovis remains poorly understood. The presence of M. bovis DNA, not necessarily viable, in environmental matrices, such as soil, sediments, water, grass, corn and hay, has been reported in several studies (Adams, Bolin, Fine, Bolin, & Kaneene, 2013; Barasona et al, 2017; Barbier, Boschiroli, et al, 2016; Barbier, Rochelet, Gal, Boschiroli, & Hartmann, 2017; Fine, O'Brien, Winterstein, & Kaneene, 2011; Santos, Santos, et al, 2015). Substrate contamination is believed to be the result of urine, faeces, saliva and/or nasal excretion by infected animals.…”
Section: Drivers Of Animal Tb Heterogeneitymentioning
confidence: 93%
“…The temperature of air and soil, but also the evapotranspiration rate, is among the most consistent positively associated variables with the probability of detecting MTC DNA in environmental samples. M. bovis has been found in higher concentration in moderate temperature and high water content, opposite to the characteristic high temperature and low water content of the dry season in summer (Adams et al, 2013; Barbier, Boschiroli, et al, 2016; Barbier et al, 2017; Santos, Almeida, Gortázar, & Correia‐Neves, 2015; Santos, Santos, et al, 2015; Young, Gormley, & Wellington, 2005). Besides, shade has been correlated with persistence of environmental M. bovis due to the maintenance of high water content and moderate temperature, but also due to low sunlight association with low ultraviolet radiation, leading to less cell stress and mutations, improving bacterial survival (Rodríguez‐Hernández et al, 2016).…”
Section: Drivers Of Animal Tb Heterogeneitymentioning
confidence: 99%
“…Mycobacterium bovis , the causal agent of bTB, can persist in the environment and this may contribute to further infection in domesticated livestock and wildlife (Courtenay et al, 2006, King et al, 2015). Infected animals shed to the environment via aerosol, urine and faeces, with a growing body of evidence suggesting that environmental M. bovis could play an important role in the persistence of this disease (Wellington and Courtenay, 2014, Duffield and Young, 1985, King et al, 2015, Barbier et al, 2017). Previous studies report the molecular detection of M. bovis in environmental faecal samples from the European badger ( Meles meles ) upwards of 15 months after excretion (Young et al, 2005).…”
Section: Introductionmentioning
confidence: 99%